Contributions to Dogri phonetics and phonology - Ghai, Ved Kumari (Annual Report of the Institute of Phonetics University of Copenhagen, 1980)
The present paper deals with some selected problems of Dogri phonetics and phonology. Section 1 contains a general introduction. Section 2 contains a formant analysis of oral vowels (2.2), a discussion of the distinctive features of vowels, in particular the relative constancy of the concomitant features length and centralization (2.3), a statement of the distribution of vowel phonemes with a discussion of the occurrence of peripheral (long) vowels before geminated consonants (2.4), and a discussion of the phonological interpretation and the phonetic manifestation of pairs of the type [ˈɡəlɑː] [ɡəˈlɑː] as a difference in length or stress. Section 3 treats the problems of consonant gemination and consonant weakening with an account of the historical background (3.2), and a discussion of the relation to syllable division (3.3) and of the interpretation of one of the grades as basic (3.4). 3.5 and 3.6 deal with the phonetic manifestation of consonant gemination and weakening, respectively.